Augmented inertial measurements for analysis of javelin throwing mechanics - Särkkä, O.; Nieminen, T.; Suuriniemi, S.; Kettunen, L. (Sports Engineering, 2016)
This paper examines the exploitation of inertial measurements to analyze javelin throwing mechanics. The main objective was to demonstrate that consumer-grade inertial navigation systems, augmented with some position and attitude data obtained from a video sequence, yield detailed information of the mechanics of javelin throwing. Especially, such a system makes it possible to analyze the momentary force and power exerted on the javelin during the acceleration phase. Although the presented system is a pilot, leaving space for further improvements, it already reveals the potential of inertial navigation systems to sports. In practise, an inertial measurement unit was embedded inside the tip of the javelin to determine the javelin`s momentary attitude, position, and velocity. Graphs on the speed and angular velocity about the longitudinal axis of the javelin during the whole performance are presented. The maximum estimated release speed and release angular speed were 28.02 m/s and 215.9 rad/s, respectively. The acceleration phase trajectory of the javelin and its deviation from a straight line path are demonstrated. Additionally, the momentary forces and powers are shown and the effect of aerodynamic forces on the projectile is specified. The magnitude of the maximum tangential forces and accelerating powers were 364 N and 9.76 kW. The duration and length of the acceleration phase trajectory varied between 223 and 231 ms, and 2.48 and 2.75 m. To estimate the accuracy of the inertial measurements, the acceleration phase results were compared to measurements made with high-speed cameras.